1993
DOI: 10.1021/j100122a020
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the gas-phase kinetics of the reaction potassium + sulfur dioxide + argon

Abstract: The recombination of atomic potassium, K(42S), with SO2 has been investigated at about 863 K, in a bath of Ar at pressures from 20 to 690 mbar. K was generated by flash photolysis of KI vapor and monitored by time-resolved resonance absorption of a D-line at 766 nm under pseudo-first-order conditions. The measured pseudo-second-order rate constants lie in the low-pressure and falloff regions and were fitted with an empirical RRKM expression to yield ko = 5.9 X cm6 s-l and k, = 6.2 X 1O-l0 cm3 s-l. Error limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Ramondo and Bencivenni 9 later reported the results of unrestricted Hartree-Fock calculations for SO 2 Ϫ and NaSO 2 , which were consistent with that assignment. A recent gas-phase kinetic study 10 of the KϩSO 2 reaction also yielded evidence for the formation of a long-lived KSO 2 complex, and the associated Hartree-Fock calculations suggested that the structure of KSO 2 , like that of NaSO 2 , is planar, with C 2v symmetry. Recent photoionization/Penning ionization studies in this laboratory have led to stabilization in a neon matrix of sufficient concentrations of a wide variety of molecular cations and anions for infrared spectroscopic detection.…”
Section: Somentioning
confidence: 98%
“…Ramondo and Bencivenni 9 later reported the results of unrestricted Hartree-Fock calculations for SO 2 Ϫ and NaSO 2 , which were consistent with that assignment. A recent gas-phase kinetic study 10 of the KϩSO 2 reaction also yielded evidence for the formation of a long-lived KSO 2 complex, and the associated Hartree-Fock calculations suggested that the structure of KSO 2 , like that of NaSO 2 , is planar, with C 2v symmetry. Recent photoionization/Penning ionization studies in this laboratory have led to stabilization in a neon matrix of sufficient concentrations of a wide variety of molecular cations and anions for infrared spectroscopic detection.…”
Section: Somentioning
confidence: 98%
“…This means H atoms are being regenerated and a plausible reaction scheme involves decomposition of the stabilized adduct back to H + CS 2 : H → diffusion loss rate constant k diff (10) C S 2 H → loss without H regeneration rate constant k 11 (11) The integrated biexponential rate law is [22]…”
Section: Resultsmentioning
confidence: 99%
“…Details of our apparatus for laser flash photolysis experiments with time-resolved resonance fluorescence detection of atomic hydrogen, including with other sulfur-containing species, have been provided previously [10][11][12][13][14] and so the method is outlined here. Inside a heated stainless steel reaction cell, H atoms are created by pulsed photolysis of a precursor at 193 nm, ammonia (NH 3 ) in this case, and then react with a large excess of CS 2 which is therefore effectively at constant concentration.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For example, the fine-structure splitting (Dl) of Li is only 0.015 nm or 10 GHz, whereas in K, it is 3.4 nm and in Rb, 14.7 nm [227]. The hyperfine splitting broadens the Doppler absorption profile of K from a halfwidth at full maximum (HWFM) of 0.39 GHze0.45 GHz at 298 K. However for Rb, the splitting distorts even the pressurebroadened absorption lines at 1 bar, as shown by comparing measured Rb(D2) absorption profiles in a combustor at 1273 K and in a low-pressure (<1 mbar), room-temperature cell; in the latter case, the four hyperfine lines of 87 Rb and 85 Rb were clearly resolved.…”
Section: Fundamentalsmentioning
confidence: 96%
“…The reactions of sodium atoms with oxygen and nitrous oxide have been the most frequently studied [73e83], but reactions with SO 2 have also been investigated [84,85]. Kinetic studies of alkali species in flames are reported in Refs.…”
Section: Metalsmentioning
confidence: 99%